Advocate Role in Ensuring Justice in Criminal Proceedings: Peran Advokat dalam Menjamin Keadilan dalam Proses Peradilan Pidana - Muhammad Naufal Fatchurrahman; Emy Rosnawati (Academia Open, 2025)
General Background: Criminal justice systems rely on multiple law enforcement actors, including advocates, to safeguard legal rights and uphold fairness during judicial processes. Specific Background: In Indonesia, advocates serve as legal counsel responsible for defending defendants, ensuring due process, and maintaining adherence to professional ethics while operating alongside police, prosecutors, and judges. Knowledge Gap: Despite their formal status as law enforcers, limited empirical insight exists into the practical challenges advocates face, particularly regarding ethical dilemmas, institutional pressures, and evolving legal contexts. Aims: This study seeks to explore advocates’ roles, challenges, defense strategies, and perspectives on legal reform in criminal cases through an in-depth interview with a legal practitioner. Results: Findings indicate that advocates encounter bureaucratic obstacles, public pressure, threats, and potential interference from other authorities, which may compromise professional independence. Effective defense relies on comprehensive investigative approaches, strong client communication, and strict adherence to ethical standards. The study also highlights the necessity of legal accompaniment for suspects facing serious charges and underscores concerns about outdated legislation in addressing modern crimes such as cyber offenses. Novelty: By presenting practitioner-based insights, the study illuminates the intersection of professional ethics, procedural justice, and legislative adequacy within real criminal case handling. Implications: Periodic legal reform, clearer recognition of advocates’ institutional position, and inclusion of legal practitioners in legislative processes are essential to build a responsive and equitable criminal justice system. Highlights: Legal practitioners confront administrative complexity, societal pressure, and security risks during case handling. Thorough evidence gathering and close client consultation form the basis of defense preparation. Regulatory updates are required to address technological developments and reduce discriminatory provisions. Keywords:Advocate Role; Criminal Justice System; Legal Defense; Professional Ethics; Legal Reform